The Role of Accounting Information Systems in Enhancing the Transparency of Sharia Financial Reporting - Suriyati, Andi; Lidyah, Rika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Financial transparency is a crucial element in maintaining public trust in Islamic financial institutions. Accounting Information Systems (AIS) play a significant role in creating accurate, timely, and Sharia-compliant financial reporting processes. This article discusses how the implementation of integrated AIS can enhance transparency and accountability in the financial reporting of Islamic financial institutions. Using a qualitative approach through literature review, the article highlights the role of information technology in supporting good governance practices and ensuring compliance with Islamic accounting standards. The findings indicate that effective utilization of AIS can minimize errors, improve operational efficiency, and strengthen institutional accountability to stakeholders.